2012
DOI: 10.1590/s0103-51502012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a physical therapy home-based exercise program for Parkinson's disease

Abstract: INTRODUCTION: Parkinson's disease (PD) is a neurological disorder that causes loss of functional abilities and independence. The aim of this study was to evaluate the effects of a physical therapist-supervised home-based exercise program in patients with PD using the UPDRS scale. MATERIALS AND METHODS: Thirty-three PD patients in the 1.5 to 3 Hoehn and Yahr stages participated in the trial. The patients and their relatives received a booklet with a 12-week home program, with a series of strengthening, stretchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
0
10
0
9
Order By: Relevance
“…Previous studies evaluating a self-supervised home-based exercise program found positive effects on the ADL and UPDRS motor examination sections (13,(15)(16)(17) as well as on QoL (15,16,18). All of them provided a manual with exercises on the program, but they varied in the form of monitoring and most of them did not make it clear whether the orientation of the exercises was individualized or in a group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies evaluating a self-supervised home-based exercise program found positive effects on the ADL and UPDRS motor examination sections (13,(15)(16)(17) as well as on QoL (15,16,18). All of them provided a manual with exercises on the program, but they varied in the form of monitoring and most of them did not make it clear whether the orientation of the exercises was individualized or in a group.…”
Section: Discussionmentioning
confidence: 99%
“…Among the advantages of this program are the convenience of being able to perform the exercises at the desired moments, not having to go to a rehabilitation unit and reducing the direct cost to the patient (13,(15)(16)(17). The latter has assumed even greater importance in our population since it is predominantly low-income (33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations